Feasibility Analysis of Argo Parahyangan Replacement Project in PT Kereta Api Indonesia (Persero) - Manurung, Chaterina; Aliludin, Arson (The Indonesian Journal of Business Administration, 2014)
Abstract. Mobility of people to travel is very high in this modern era. PT. Kereta Api Indonesia (Persero) is one of the state-owned companies that engaged in transportation and has been railway operator for Java and Sumatra region. One of the most busy and favorable route for railway passenger service is Jakarta-Bandung. Cipularang Toll that constructed in 2005 made significant impact to PT. Kereta Api Indonesia (Persero). The travel time through the corridor has been much improved for toll-road travelers than for rail travelers, so it gives impact that a major part of the railway customers have been diverted to toll-road.To improve the reliability of Argo Parahyangan train, there is a project to replace the existing train and add one train. To know the value and benefit of this project, feasibility study should be done through several analyses. The techniques that used to do investment evaluation are Payback Period, Net Present Value, Internal Rate of Return, and Profitability Index. Cash inflow and cash outflow for calculating the feasibility of project are using incremental analysis which is taking the differences between existing condition and proposed condition.From the feasibility analysis conducted, it can be concluded that Argo Parahyangan replacement project is feasible to run. It could be seen from a positive NPV, IRR exceeds the cost of capital, PI more than one, and project payback is faster than the economic life of trains.Â Keywords: Railway Industry, Argo Parahyangan, Incremental Analysis, Feasibility Study, Monte Carlo Simulation.